The utilization of audio-visual media in optimizing learning outcomes in Catholic religious education and ethics for grade XII students at Vocational School Sanggau - Libertus Fransiskus Yadi; Rezkie Zulkarnain; Gustaf Hariyanto (Privietlab, 2026)
This study addressed challenges in schools regarding learning outcomes in Catholic Religious Education and Ethics or Pendidikan Agama Katolik and Budi Pekerti (PAK and BP) that have not reached the Criteria for Achievement of Learning Objectives or Kriteria Ketercapaian Tujuan Pembelajaran (KKTP), alongside insufficient utilization of learning media, particularly audio-visual media. This study aimed to examine the influence of audio-visual media on learning outcomes in PAK and BP for grade XII students at Vocational School Sanggau. Employing a quasi-experimental design with a non-randomized assignment, this study utilized a post-test-only control group structure. Data were collected through a multiple-choice assessment administered to each class after the completion of the learning process. Assessment scores were analyzed using SPSS 27 for Windows to evaluate normality, homogeneity, and independent-sample t-tests. The results demonstrated that learning achievement completeness was 38.0% in the control class and 70.4% in the experimental class. The data were normally distributed (p > 0.05) and homogeneous (p = 0.082 > 0.05). Independent sample t-test results revealed a significance value of 0.014 < 0.05, thus accepting H₁ and rejecting H₀, indicating that audio-visual media significantly influence learning outcomes in PAK and BP for Grade XII students at Vocational School Sanggau. The effect size analysis using Hedges' g yielded a point estimate of 0.732, which indicated a large effect size. Therefore, this study concludes that audio-visual media interventions have substantial effects on learning outcomes.